2022
DOI: 10.48550/arxiv.2208.03946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new study on a type Iax stellar remnant and its probable association with SN 1181

Abstract: We report observations and modelling of the stellar remnant and presumed double-degenerate merger of Type Iax supernova SN 1181 AD. It is the only known bound stellar SN remnant and the only star with Wolf-Rayet features that is neither a planetary nebula central star nor a massive Pop I progenitor. We model the unique emission-line spectrum with broad, strong O vi and O viii lines as a fast stellar wind and shocked, hot gas. Non-LTE wind modeling indicates a mass-loss rate of ∼ 10 −6 M yr −1 and a terminal ve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…The electron density sensitive [S II] λ6716/λ6731 line ratio was measured for the brightest filaments and found to range between 1.4 to 0.9 indicating electron densities between 100 − 700 cm −3 with an average ratio around 1.2 (300 cm −3 ) (Osterbrock & Ferland 2006). Although Ritter et al (2021) do not quote electron densities measured from their GTC/OSIRIS observed [S II] line ratios, Lykou et al (2022) states the average [S II] derived density value from those data was 120 cm −3 , which is a bit lower than the average we found. Also, in the few cases where there was a significant brightness difference between the ends of a filament, the filaments' brightest portion displayed the lowest velocity, suggesting the densest portions of these filaments lies closer in to the remnant's center.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The electron density sensitive [S II] λ6716/λ6731 line ratio was measured for the brightest filaments and found to range between 1.4 to 0.9 indicating electron densities between 100 − 700 cm −3 with an average ratio around 1.2 (300 cm −3 ) (Osterbrock & Ferland 2006). Although Ritter et al (2021) do not quote electron densities measured from their GTC/OSIRIS observed [S II] line ratios, Lykou et al (2022) states the average [S II] derived density value from those data was 120 cm −3 , which is a bit lower than the average we found. Also, in the few cases where there was a significant brightness difference between the ends of a filament, the filaments' brightest portion displayed the lowest velocity, suggesting the densest portions of these filaments lies closer in to the remnant's center.…”
Section: Resultsmentioning
confidence: 98%
“…The remnant's hot central star, called J005311 based on its J2000 coordinates (α=00 h 53 m 11.2 s , δ=+67 • 30 2.4 ), has been proposed to be either a high mass white dwarf (WD), a super-Chandrasekhar-mass WD, or the result of a double degenerate merger which resulted in a SN Iax explosion (Gvaramadze et al 2019;Kashiyama et al 2019;Oskinova et al 2020;Lykou et al 2022). While the convergence point of the remnant's filaments lies very close to Pa 30's hot central star, a few of the brighter filaments do not appear in perfect alignment with the star's current position.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations